Pengaruh Pelatihan Kerja Dan Lingkung Kerja Terhadap Kinerja Pada PT Brammco Olam Sempurna Ciledug Tangerang - Mochamad Yusril Irvanda; Fathan Arif (Yayasan Sahabat Cendekia Jaya, 2024)
Purpose. The research aims to determine the influence of work training and work environment on employee performance at PT Brammco Olam Sempurna Ciledug Tangerang, both partially and simultaneously. Methods. The research method used in this research is quantitative. The sampling method used in this research was a saturated sample, where the sample was all 55 employees of PT Brammco Olam Sempurna Ciledug Tangerang. The data collection method used in this research is primary data. The primary data taken is data from the answers of 55 respondents. Results. The results of this research show that work training has a partial effect on the performance of PT Brammco Olam Sempurna Ciledug Tangerang employees as evidenced by the calculated t value > t table or (7.393 > 2.006). This is also reinforced by the Sig value. < 0.05 or (0.00 < 0.05). The work environment has a partial effect on the performance of PT Brammco Olam Sempurna Ciledug Tangerang employees as evidenced by the calculated t value > t table or (12.835 > 2.006). This is also reinforced by Sig. < 0.05 or (0.000 < 0.05). Work Training and Work Environment simultaneously influence the performance of PT Brammco Olam Sempurna Ciledug Tangerang employees as evidenced by the calculated F value > F table or (88.081 > 3.17), this is also reinforced by the Sig value < 0.05 or (0.000 < 0.05). Implications. Job Training and Work Environment simultaneously influence the performance of PT Brammco Olam Perfect Ciledug Tangerang City employees as evidenced by the calculated F value > F table or (88.081 > 3.17), this is also reinforced by the Sig value. < 0.05 or (0.000 < 0.05). Keywords. Work Training; Work Environment; Employee performance